Words apart: Standardizing forestry terms and definitions across European biodiversity studies - Giovanni Trentanovi; Thomas Campagnaro; Tommaso Sitzia; Francesco Chianucci; Giorgio Vacchiano; Christian Ammer; Michał Ciach; Thomas A. Nagel; Miren del Río; Yoan Paillet; Silvana Munzi; Kris Vandekerkhove; et al. (Forest Ecosystems, 2023)
Forest biodiversity studies conducted across Europe use a multitude of forestry terms, often inconsistently. This hinders the comparability across studies and makes the assessment of the impacts of forest management on biodiversity highly context-dependent. Recent attempts to standardize forestry and stand description terminology mostly used a top-down approach that did not account for the perspectives and approaches of forest biodiversity experts. This work aims to establish common standards for silvicultural and vegetation definitions, creating a shared conceptual framework for a consistent study on the effects of forest management on biodiversity. We have identified both strengths and weaknesses of the silvicultural and vegetation information provided in forest biodiversity studies. While quantitative data on forest biomass and dominant tree species are frequently included, information on silvicultural activities and vegetation composition is often lacking, shallow, or based on broad and heterogeneous classifications. We discuss the existing classifications and their use in European forest biodiversity studies through a novel bottom-up and top-driven review process, and ultimately propose a common framework. This will enhance the comparability of forest biodiversity studies in Europe, and puts the basis for effective implementation and monitoring of sustainable forest management policies. The standards here proposed are potentially adaptable and applicable to other geographical areas and could be extended to other forest interventions.